2014
DOI: 10.3846/bjrbe.2014.20
|View full text |Cite
|
Sign up to set email alerts
|

Peculiarity of low noise pavement design under Lithuanian conditions

Abstract: The paper gives a detailed overview and analysis of road transport noise propagation, noise composition and impacts on the living conditions. Road transport noise has been rapidly growing and the traditional noise abatement solutions, such as noise barriers, are not always suitable and cost-effective for particular road infrastructure. One of the most promising and effective solutions is the use of low noise pavements. Presently, low noise pavements are not being used in Lithuania but expected to have a good e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
1
2
0
1
Order By: Relevance
“…The behavior of the different sound absorption peaks might indicate that some asphalt samples show better sound absorption within a specific low-frequency range from 400 Hz to 700 Hz. Experimental studies from different investigations on asphalt mixtures showed similar sound absorption behavior at different frequencies [45,46], confirming that the peaks of maximum sound absorption are associated with the low-frequency range.…”
Section: Volumetric Characterization Permeability and Macrotexturesupporting
confidence: 53%
“…The behavior of the different sound absorption peaks might indicate that some asphalt samples show better sound absorption within a specific low-frequency range from 400 Hz to 700 Hz. Experimental studies from different investigations on asphalt mixtures showed similar sound absorption behavior at different frequencies [45,46], confirming that the peaks of maximum sound absorption are associated with the low-frequency range.…”
Section: Volumetric Characterization Permeability and Macrotexturesupporting
confidence: 53%
“…Annual social economic expenses of traffic noise exceed 40 billion EUR, of which 90% were caused by road-transport-generated noise [2]. Road transport noise is caused by noise from propulsion, aerodynamic resistance, and noise from tire and pavement interactions [3][4][5]. However, tire/road noise due to tire and pavement interactions is dominant at speeds above 40 km/h [6] and is influenced by four major factors [7][8][9][10]: pavement surface characteristics (surface texture, friction, aggregate properties, air-void content (porosity), pavement materials and their properties, pavement age, and durability); tire characteristics (tire dimensions, rubber hardness, trend pattern, tire age and wear, studs, and tire number); environmental factors (temperature, moisture, wind, water film thickness, and dust); and driver-controlled factors (driving speed, tire load and pressure, tangential forces, and acceleration).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the laboratory research, testing results and estimations that developed low noise asphalt mixtures for regional climate conditions should reduce noise by 2-4 dBA (Vaitkus et al 2014), it was decided to construct test sections and perform further research of low noise pavements. The aim is to increase the level of living quality of population by testing low noise pavements in real traffic and environmental conditions, evaluating noise reduction characteristics dependent on asphalt mixture type and duration and level of exploitation.…”
Section: Test Road Of Low Noise Pavementsmentioning
confidence: 99%